Do cigarette graphic warnings encourage smokers to attend a smoking cessation programme: a quasi-experimental study. Issue 1 (2nd December 2016) - Guydish, Joseph; Tajima, Barbara; Le, Thao; Henderson, Catherine; Yip, Deborah; Gruber, Valerie; Garcia, Wayne; Delucchi, Kevin L
Abstract : Objective: This study assessed whether exposure to cigarette graphic warning labels (GWLs) increased attendance to a smoking cessation programme. Method: From 2014 to 2016, alternating cohorts of smokers in 3 residential drug treatment programmes received either GWLs (experimental) or transparent (control) labels placed on their cigarette packs for 30 days. The primary outcome was the proportion of participants who chose to attend a smoking cessation group after the labelling period. Results: The sample (N=601) was 72.6% male, with a mean age of 41.9 (SD=11.16) and included African-American (37%), White (29.4%) and Hispanic (19.6%) participants. While similar on most measures, controls were more likely to be married, had been in the treatment programme longer and registered higher on expired carbon monoxide (CO). After labelling, the proportion attending at least one cessation group was 26% in the experimental condition and 18.8% among controls. In an intent-to-treat analysis adjusting for group differences at baseline, and for 2 levels of nesting, those who received GWLs were more likely than controls to attend the smoking cessation group (OR=1.58, 95% CI 1.02 to 2.44). Conclusions: Smokers who received GWLs on their cigarette packs were more likely to attend a cessation programme. Thus, this study is one of the first to document a change in a directly observed behavioural outcome as a function of month-long exposure to cigarette pack GWLs.